Karakteristik Fisik dan Performa Pembakaran Briket Biocoal Berbasis Campuran Biomassa Ranting Pohon dan Batubara pada Berbagai Komposisi - Zana Azalia Maktub; Tamrin Tamrin; Budianto Lanya; Sapto Kuncoro (Jurnal Agricultural Biosystem Engineering, 2026)
The utilization of biomass as a renewable energy source has gained increasing attention as an alternative to fossil fuels. This study aimed to evaluate the effect of tree branch biomass proportion on the physical characteristics and combustion performance of biocoal briquettes produced from biomass–coal blends. Four briquette formulations containing 16.0%, 31.9%, 47.7%, and 63.7% tree branch biomass were prepared and tested for density, impact resistance, tensile strength, compressive strength, and combustion rate. The results showed that biomass composition significantly affected the physical and combustion properties of the briquettes. The highest density was obtained at 16.0% biomass content (940.84 kg/m³), while the lowest density was observed at 47.7% biomass content (883.08 kg/m³). The briquette containing 47.7% biomass exhibited the best mechanical properties, characterized by the lowest number of fragments after impact testing (3.4 pieces), the highest tensile strength (115,710.61 N/m²), and the highest compressive strength (168,541.37 N/m²). Meanwhile, the highest combustion rate was achieved by the briquette containing 63.7% biomass, reaching 2.37 g/min. Compared with commercial coal briquettes, the combustion performance of the 63.7% biomass briquette approached that of super briquettes (2.57 g/min) and exceeded that of pure coal briquettes (2.09 g/min). Overall, a biomass proportion of 47.7% was considered optimal in terms of physical and mechanical properties, while 63.7% biomass provided the best combustion performance. These findings demonstrate the potential of tree branch biomass as a sustainable feedstock for biocoal briquette production.